A Review on the Exraction Methods of Extracts and Phytochemicals from Eurycoma longifolia (Tongkat Ali Jack) - Elhag, Husam Eldin Elhag Abugabr; Ahmad Ziad, Sulaiman; Azilah, Ajit (Universiti Malaysia Pahang, 2016)
Eurycoma longifolia (Tongkat Ali Jack) is a valuable source of medicinal metabolites such as eurycomanone, which is an important ingredient in food supplement and drugs. The plant extracts and products are known for their aphrodisiac activities beside antimalarial, antiulcer, antitumor and antibacterial activities. Procedures that are involved in extraction of this plant focus on onconventional methods such as maceration and decoction while nonconventional procedures such as microwave and ultrasonic assisted extraction methods are still to be deeply investigated. Nonconventional methods are highly nominated to increase the extract yield and subsequently the concentration of major metabolites, a concept that is investigated in the field of chemical engineering